Tiered Information Disclosure: An Empirical Analysis of the Advance Peek into the Michigan Index of Consumer Sentiment. Issue 3 (4th July 2019) - Wu, Weishao; Liu, Wenchien; Suardi, Sandy; Chang, Yuanchen
Abstract: This paper studies market microstructure implications of informed high‐frequency traders (HFTs) from two seconds of advance peek into the Michigan Index of Consumer Sentiment (ICS), provided by Thomson Reuters to its elite customers. Using individual stocks in the NASDAQ data set, we show how HFTs trade around ICS events. We find that liquidity demanders during two seconds of advance peek earn substantive profits, which are consistent with the notion that HFTs' informational advantages may increase adverse selection costs for other market participants. This evidence elucidates the debate on regulatory oversight and its role in circumventing the potentially adverse effects from an advance peek into ICS.